Contribution of Imaging in Diagnosis of Primitive Cyst Hydatid in Unusual Localization: Pleura—A Report of Two Cases - Fatima Zahra Mrabet; Jihane Achrane; Yassir Sabri; Fatima Ezzahra El Hassani; Sanaa Hammi; Jamal Eddine Bourkadi (Case Reports in Radiology)
Hydatic disease has always been the most common in countries where large amount of sheep and cattle is raised, but increased travel and immigration have made this condition a serious worldwide public problem. Cyst hydatid may affect all parts of the human body like the heart, the bone marrow, the eye, the brain, the kidney, and the spermatic cord. Humans can become infested by accidentally ingesting the eggs that are passed in the feces from definitive hosts (usually a canid, such as a wolf, fox, or dog). Even in endemic countries, the primitive pleural hydatid cyst is exceptional, and it is very difficult to distinguish from other pleural and parietal cystic masses especially that in majority of cases the immunologic tests are negative. We report two cases of pleural hydatid cyst discovered in two young patients, with a nonspecific clinical presentation. The interest of this paper is to raise the primordial role of imaging in the positive diagnosis of primary pleural hydatid cyst.